2012
DOI: 10.1590/s0004-27302012000900006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical judgment to estimate pretest probability in the diagnosis of Cushing's syndrome under a Bayesian perspective

Abstract: Objective: To estimate the pretest probability of Cushing's syndrome (CS) diagnosis by a Bayesian approach using intuitive clinical judgment. Materials and methods: Physicians were requested, in seven endocrinology meetings, to answer three questions: "Based on your personal expertise, after obtaining clinical history and physical examination, without using laboratorial tests, what is your probability of diagnosing Cushing's Syndrome?"; "For how long have you been practicing Endocrinology?"; and "Where do you … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…This underlines the importance of the endocrinologist who is familiar with the clinical features of the disease. In our study, the diagnosis of CD was made in 69.9% of cases by an endocrinologist and even attendants of endocrinology meetings rated their ability to clinically diagnose CS as dependent on their years of clinical practice (14).…”
Section: European Journal Of Endocrinologymentioning
confidence: 73%
See 1 more Smart Citation
“…This underlines the importance of the endocrinologist who is familiar with the clinical features of the disease. In our study, the diagnosis of CD was made in 69.9% of cases by an endocrinologist and even attendants of endocrinology meetings rated their ability to clinically diagnose CS as dependent on their years of clinical practice (14).…”
Section: European Journal Of Endocrinologymentioning
confidence: 73%
“…overweight and insulin resistance), Bayes' theorem shows how the initially very low previous probability of a true diagnosis of CS (because of the rarity of the disease) is influenced, when a new symptom or test result is added to the diagnostic process (12,13). In this context, the studies by Nugent and other authors demonstrated how the probability of an overweight patient being correctly diagnosed with CS increases considerably when the specific symptoms of muscle weakness and ecchymosis or certain laboratory results are included in the statistical approach (12,13,14). Next to the use of specific symptom combinations, it might also be helpful to include the speed of symptom-onset and progression in clinical reasoning.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…17,39,54 The predictor variables included in our study represent the clinical information typically used by veterinarians in practice to formulate a perceived "pretest" probability of disease. 55,56 The dogs included in our study were required to have been suspected of having Cushing's in the EHRs therefore were presumably perceived to have a greater "pretest" probability of Cushing's by the attending veterinarian. The tool could perform differently at varying thresholds of "pretest" probabilities, used by differing veterinarians to consider the animal as a…”
Section: Prediction Toolmentioning
confidence: 99%
“…Their prediction of the presence of a disease improves with clinical experience,18 but it is not clear whether this is matched by an improved understanding of probability.…”
Section: Introductionmentioning
confidence: 99%